Following public finances: The mirage of MDBs countercyclicality - Leopoldo Avellán; Arturo José Galindo Andrade; Giulia Lotti (Inter-American Development Bank (IDB), 2020)
Fiscal policy and net capital inflows in developing countries are procyclical. A large amount of literature has examined this phenomenon and explored its consequences for aggregate fluctuations. Multilateral development banks (MDBs) are an important source of external finance for governments and hence play a key role in financing the execution of fiscal policy. Hence, understanding the behavior of MDB flows is key to gauge their contribution to macroeconomic volatility. This paper investigates the co-movement of sovereign lending from MDBs and private creditors with government expenditure, and finds that multilateral sovereign lending follows government expenditure, and that this correlation does not change if the government is running a surplus or a deficit. This finding raises doubts on the feasibility of MDBs to be counter-cyclical, unless the governments themselves implement counter-cyclical fiscal policies.
Keywords: F21; F34; F42; F44; F53; 330; International government debt; capital flows; counter-cyclicality; multilateral development banks